2017
DOI: 10.1117/2.1201703.006874
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineered lone-pair active photocatalysts for more efficient water splitting

Abstract: A whole family of promising nanoengineered photocatalysts have been identified to enable the generation of solar fuels, hydrogen, and oxygen via artificial photosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In this topical review, we summarize the development of visible light semiconductor photocatalysts from an electronic structure perspective emphasizing the critical role of interfaces. We focus on the development of nano-engineered nanowire (NW)/quantum dot (QD) heterostructures that have recently demonstrated to be viable photocatalytic architectures capable of efficacious hydrogen evolution [13,[35][36][37]. The topochemical synthesis of ternary M x V 2 O 5 nanowires, where M is a lone pair active (N − 2)s 2 ion, presents a new class of charge-separation components where improved band alignment with the H 2 O/O 2 redox can be engineered.…”
Section: Rational Development Of Pec Materials: Electronic Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…In this topical review, we summarize the development of visible light semiconductor photocatalysts from an electronic structure perspective emphasizing the critical role of interfaces. We focus on the development of nano-engineered nanowire (NW)/quantum dot (QD) heterostructures that have recently demonstrated to be viable photocatalytic architectures capable of efficacious hydrogen evolution [13,[35][36][37]. The topochemical synthesis of ternary M x V 2 O 5 nanowires, where M is a lone pair active (N − 2)s 2 ion, presents a new class of charge-separation components where improved band alignment with the H 2 O/O 2 redox can be engineered.…”
Section: Rational Development Of Pec Materials: Electronic Perspectivementioning
confidence: 99%
“…In 2014 Piper et al, demonstrated how the revised oxygen mediated lone pair distortion mechanism could be synthetically controlled by incorporating Pb 2+ ions into the structure of V 2 O 5 nanowires, such that the ionization potential could be raised closer to the H 2 O/O 2 redox potential [82]. Chemical considerations would suggest that interfacing the synthetic lone pair active β-Pb x V 2 O 5 nanowires with dedicated light harvesting quantum dots would present an opportunity to rationally engineer efficient photo-excited charge separation necessary for photocatalysis [35]. For synthetic lone pair metal oxides such as β-Pb x V 2 O 5 , the valence band alignment could possibly be modified by chemical substitution of the Pb 2+ ion with alternate (N − 2) post-transition metal ions [82], significantly altering the resultant thermodynamics and kinetics of the photoexcited carriers and thereby the resulted photocatalysis [13,36,37].…”
Section: Revised Oxygen Mediated Lone Pair Model For Post-transition ...mentioning
confidence: 99%
See 1 more Smart Citation